2019
DOI: 10.3390/met9030362
|View full text |Cite
|
Sign up to set email alerts
|

Study on Intensification Behavior of Bismuth Ions on Gold Cyanide Leaching

Abstract: Gold cyanide leaching is inefficient with conventional cyanidation. Bismuth ions can improve the efficiency of gold cyanidation by intensifying gold dissolution. The electrochemical behavior, structure information, and surface product of gold anodic dissolution were studied during the intensification of bismuth ions on gold cyanide leaching. The electrochemical analysis showed that the bismuth ions can not only improve anode current density, but also make gold dissolve at a lower potential, increase the corros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
1
1
Order By: Relevance
“…The impact of bismuth and cobalt ions on the dissolution kinetics of Zn ions in TNMs was found to be minimal ( Table 2 ), thus not affecting the surface properties of the material. This conclusion differs from the findings reported in the a study conducted by Yang [ 26 ]. These authors observed an increased dissolution of metals, such as gold, in the presence of bismuth ions.…”
Section: Discussioncontrasting
confidence: 99%
“…The impact of bismuth and cobalt ions on the dissolution kinetics of Zn ions in TNMs was found to be minimal ( Table 2 ), thus not affecting the surface properties of the material. This conclusion differs from the findings reported in the a study conducted by Yang [ 26 ]. These authors observed an increased dissolution of metals, such as gold, in the presence of bismuth ions.…”
Section: Discussioncontrasting
confidence: 99%
“…According to relevant reports, many cultural relics decorated with gold leaf were damaged to varying degrees when exposed to air. For example, the gold leaf-decorated Dazu thousand-hand Buddha statue in Chongqing, China, which was listed as a world cultural heritage site in 1999, has been seriously damaged in recent years due to the acidic climate [ 17 , 18 , 19 ]. The statue of Buddha has been in the cave for more than a thousand years.…”
Section: Introductionmentioning
confidence: 99%